Community Adaptability Tool - Securing the wealth and wellbeing of rural communities - Tanton, Robert; Phillips, Rebecca; Hogan, Anthony; Carson, Dean; Cleary, Jen; Donelly, David; Houghton, Kim (My University, 2014)
This project developed a methodology, the Community Adaptability Tool (CAT), for enabling communities to assess their socio-economic sustainability in the face of many change processes. This report describes ‘concept testing’ of the specific discipline-based (economics, demography, community development, sociology and social research) components of the CAT, as well as testing of the extent to which they could produce useful socio-economic indicators which communities could use to inform their decision making. Examples have been included of the information collected in three case study sites - Waikerie, St George and Gunnedah.
Rural Industries Research & Development Corporation (RIRDC Report) 14/041
Keywords: Life Events; Satisfaction -- Life; Social Capital -- Communities and Neighbourhoods; Disadvantage, adversity and resilience; Life Events; Satisfaction; Social Capital; Life; Communities and Neighbourhoods; Adversity and resilience; Dsiadvantage, adversity and resilience